2019
DOI: 10.1038/s41567-018-0408-1
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz-driven phonon upconversion in SrTiO3

Abstract: Direct manipulation of the atomic lattice using intense long-wavelength laser pulses has become a viable approach to create new states of matter in complex materials. Conventionally, a high frequency vibrational mode is driven resonantly by a mid-infrared laser pulse and the lattice structure is modified through indirect coupling of this infrared-active phonon to other, lower frequency lattice modulations. Here, we drive the lowest frequency optical phonon in the prototypical transition metal oxide SrTiO3 well… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
127
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(134 citation statements)
references
References 72 publications
5
127
1
1
Order By: Relevance
“…While it has been shown that parametric resonances of phonons may influence the superconducting critical temperature [73], the mechanism here is fundamentally different from the parametric amplification of light by an optically excited Higgs mode in superconductors discovered recently [21]. We further note that coherent energy transfer to a nearly silent phonon mode has been observed in a high-harmonic phonon upconversion process [43].…”
mentioning
confidence: 54%
“…While it has been shown that parametric resonances of phonons may influence the superconducting critical temperature [73], the mechanism here is fundamentally different from the parametric amplification of light by an optically excited Higgs mode in superconductors discovered recently [21]. We further note that coherent energy transfer to a nearly silent phonon mode has been observed in a high-harmonic phonon upconversion process [43].…”
mentioning
confidence: 54%
“…This effect of coherent phonons is in stark contrast to that of incoherent phonons from thermal excitations, which diminishes topological enhancement of surface transport via random lattice scattering, heating, surface-bulk charge transfer and coupling. Ultrafast phononics has been explored as a new avenue to manipulate properties of superconductors, 8 oxides, 9,10 semimetal 11 and photovoltaic semiconductors. 12 Although experimental realizations of coherent phonon generation have been explored in TIs, 7,13,14 the influence of such vibrational coherence on the surface helical transport has not been observed until now.…”
Section: Introductionmentioning
confidence: 99%
“…The terahertz (THz) frequency range lies in the microwave and infrared wavelength ranges of the electromagnetic spectrum, showing potential applications in the practical fields of spectral analysis, imaging, homeland security detection, and high-speed wireless communication (in the range of several hundred Gbit s −1 ) [1][2][3][4][5][6][7][8]. But to further substantial development of THz science and technology, there is a high demand for well-performing functional waveguide devices and components.…”
Section: Introductionmentioning
confidence: 99%